Problems and ways of improving the efficiency of surgical treatment of hiatal herniae - D. I. Vasilevskii; S. Iu. Dvoretskii; I. S. Tarbaev; A. M. Akhmatov (Вестник хирургии имени И.И. Грекова)
The objective of the study is to consider the main problems and to define the ways to improve the efficiency of surgical treatment of hiatal herniae.Material and methods. 518 patients were operated, the plasty of hiatal hernia – posterior cruroraphy – was carried out in 191 (26.9%) of patients, the prosthetic materials via the method «mesh-reinforced» were used in 327 (63.1%) of patients.Results. The general surgical complications were noted in 43 (8.3 %) patients, the delayed side effects were in 118 (22.8 %) patients, relapse of hiatal hernia were in 27 (5.9 %) patients.Conclusion. The high frequency of relapses remains the main problem in surgery of hiatal hernia.